Antiacrosin antibodies and infertility. II: gene immunization with human proacrosin to assess the effect of immunity toward proacrosin/acrosin upon protein activities and animal fertility - Veaute, Carolina Melania Isabel (2008)
Objective: To assess the effect of antiacrosin antibodies upon proacrosin/acrosin activities and animal fertility. Design: Prospective study. Setting: Basic research laboratory. Patient(s): A gene immunization (GI) model was developed; mice were injected with the sequence encoding human proacrosin (h-proacrosin), cloned in an expression vector. Intervention(s): Subcloning of h-proacrosin in a eukaryotic expression vector (promoter, CMV; leader sequence, a-1 antitrypsin; pSF2-Acro); GI of female mice with this plasmid. Main Outcome Measure(s): The following parameters were evaluated: [1] adequate conditions for GI protocols, [2] humoral response to GI with pSF2-Acro, [3] protein regions recognized by the antibodies, and [4] effect of antibodies upon proacrosin/acrosin–ZPA binding and amidase activity, and animal fertility. Result(s): Conditions of female mice GI with the proacrosin sequence were established (plasmid purification with anion exchange chromatography and 40 mg of pSF2-Acro per dose) to trigger an immune response, reaching maximum levels at week 9 after the first injection. Antibodies produced by GI recognized human and mouse sperm acrosin systems, inhibited human proacrosin/acrosin interaction with recombinant human ZPA and protease activity, and negatively affected mouse IVF and early embryonic development. In addition, mice immunized with SF2-Acro exhibited a significantly lower size of fetuses. Conclusion(s): Antiacrosin antibodies developed by using GI inhibit human proacrosin/acrosin activities and impair mouse fertility.